1995
DOI: 10.1002/ajmg.1320580303
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of arachnodactyly, disturbance of cranial ossification, protruding eyes, feeding difficulties, and mental retardation

Abstract: We have evaluated an infant with a striking combination of craniofacial anomalies, arachnodactyly, and severe developmental failure. She died at the age of 5 months during a recurrent apneic episode. She also had protruding eyes, downward slant of palpebral fissures, short upturned nose, midface hypoplasia, micrognathia, extreme under-development of the epiglottis, and severe feeding difficulties. The patient closely resembled four other previously reported patients. It is suggested that these five patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The phenotype of patients with Shprintzen-Goldberg syndrome includes craniofacial, skeletal, and other anomalies [Shprintzen and Goldberg, 1982;Sugarman and Vogel, 1981;Saal et al, 1995;Adès et al, 1995;Kosztolá nyi et al, 1995;Sood et al, 1996]. In Tables I-IV the clinical and radiologic findings on 4 new patients with SGS and the interim findings on patient 2 of the original report of Shprintzen and Goldberg [1982] are compared with those of 10 reported cases of SGS and the patients reported by Furlong et al [1987] and Lacombe and Battin [1993].…”
Section: Discussionmentioning
confidence: 95%
“…The phenotype of patients with Shprintzen-Goldberg syndrome includes craniofacial, skeletal, and other anomalies [Shprintzen and Goldberg, 1982;Sugarman and Vogel, 1981;Saal et al, 1995;Adès et al, 1995;Kosztolá nyi et al, 1995;Sood et al, 1996]. In Tables I-IV the clinical and radiologic findings on 4 new patients with SGS and the interim findings on patient 2 of the original report of Shprintzen and Goldberg [1982] are compared with those of 10 reported cases of SGS and the patients reported by Furlong et al [1987] and Lacombe and Battin [1993].…”
Section: Discussionmentioning
confidence: 95%
“… The data were taken from the present work and previous publications on SGS identified by a comprehensive search in pubmed [Sugarman and Vogel, 1981; Shprintzen and Goldberg, 1982; Furlong et al, 1987; Kozlowski et al, 1992; Lacombe and Battin, 1993; Adès et al, 1995; Kosztolanyi et al, 1995; Saal et al, 1995; Nishimura and Nagai, 1996; Sood et al, 1996; Hassed et al, 1997; Seemanova and Kozlowski, 1997; Greally et al, 1998; Mégarbané and Hokayem, 1998; Stoll, 2002; Topouzelis et al, 2003]. …”
Section: Discussionmentioning
confidence: 99%
“…At present it remains uncertain whether the two groups represent distinct disorders. Greally et al [1998] summarized the findings in 15 patients, four they reported themselves and 11 from literature [Sugarman and Vogel, 1981; Shprintzen and Goldberg, 1982; Ades et al, 1995; Kosztolanyi et al, 1995; Saal et al, 1995; Sood et al, 1996]. Two other patients were reported on since then [Hassed et al, 1997; Megarbane and Hokayem, 1998], which led the latter authors to distinguish two disorders that are characterized by craniosynostosis and marfanoid habitus: SGC type I showing intellectual disability, hypotonia, and bowed long bones; and SGS type II with normal intelligence, aortic root anomalies, and mild skeletal dysplasia.…”
Section: Discussionmentioning
confidence: 99%